Re-inventing the self: constructions of identity in Malaysian Blogosphere - Noraini Md. Yusof, (Pusat Pengajian Bahasa dan Linguistik,FSSK,UKM, 2009)
This paper discusses issues relating to constructions of identity by examining representations of the self through personal ruminations of selected Malaysian bloggers. The blog is a recent product of cyber culture which functions as a medium for the presentation of self; this virtual space offers freedom to the blogger to express issues that reflect his or her concerns. Many bloggers assume online identities to achieve visibility in cyberspace and yet remain invisible.Aspects of identity are traditionally characterized in terms of gender and interpersonal characteristics, which may include self definition or personal traits, roles and relationships,personal values or moral beliefs (Calvert, 2002). However, the emancipation and anonymity of cyberspace offers Malaysian bloggers an opportunity to re-invent themselves. In this culturally diverse and virtual community, these bloggers, not only incarnate themselves through avatars,but they also deconstruct accepted norms of gender and appropriate identities in Malaysian history to create alternative identities of themselves. The dynamic nature and constant redrawing of rules in cyber culture has sanctioned the blurring of gender lines as well as manipulation of the personal and shared past. By drawing upon Butler’s (1990b) concept of gender performativity, I will disclose instances of fluidity of gender among selected young bloggers. The deconstructive nature of New Historicism permits me to illustrate the appropriation of history as the means for a metamorphosis of the self. Thus, identifying ambivalence in the way one perceives oneself and the choices made to present one’s self to others, as well as attributing that ambivalence to social factors (such as social attitudes toward questions of gender ambiguity and appropriation of history) may bring to light issues pertaining to identity reconstruction and the implications of such trends on contemporary constructs of the self in Malaysia.